Let the games begin and go on - Matos, M. C. P.; Ferreira, M. A. M.; Filipe, J. A. (International Journal of Business and Systems Research, 2018)
Real life is a bigger game in which what a player does early on can affect what others choose to do later on. In particular we can strive to explain how cooperative behaviour can be established as a result of rational behaviour. When engaged in a repeated situation, players must consider not only their short-term gains but also their long-term payoffs. The general idea of repeated games is that players may be able to deter another player from exploiting his short-term advantage by threatening a punishment that reduces his long-term payoff. The aim of the paper that supports this abstract is to present and discuss dynamic game theory. There are three basic kinds of reasons, which are not mutually exclusive, to study what happens in repeated games. First, it provides a pleasant and a very interesting theory and it has the advantage of making us become more humble in our predictions. Second, many of the most interesting economic interactions repeated often can incorporate phenomena which we believe are important but which are not captured when we restrict our attention to static games. Finally, economics, and equilibrium based theories more generally, do best when analysing routinized interactions.